Dynamic axial and oblique crushing og foam-filled aluminium conical tubes - Fauziah Mat (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2015)
The aim of this study was to investigate the response of conical aluminium tubes subjected to dynamic axial and oblique loading. The effect of foam filling on the energy absorption for variation in geometry, tube material and filler density was evaluated and discussed. This study employs a nonlinear finite element model which was validated against experimental data. Main trends in the experimental results are well captured by the FE results under dynamic axial and oblique loading.